The Relationship Between Perceptions About Consuming Cigarettes With The Intention Of Smoking In Adolescents At Upt Smpn 1 Bangsal Kabupaten Mojokerto - Faisal ibnu (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
dear my editor this is my journal. thanks